Deregulierung und/oder Internationalisierung?: Deutsche Qualitätssicherung im Zeichen Bolognas - Serrano-Velarde, Kathia (Berliner Journal für Soziologie, 2008)
The following article deals with the emergence of a national quality assurance system for the higher education sector. For 10 years, national and international reform processes have interfered in the structuration of German evaluation and accreditation. Whereas national reform discourses highlight the necessity to deregulate higher education steering, international reform programmes (such as the Bologna process) focus on issues of compatibility and international comparability of national quality assurance systems. How do national and European reform agendas impact on the organisation of a national quality assurance system and to what extend do economic considerations play a role? An institutional economic study of the creation and evolution of German evaluation and accreditation agencies identifies the national and international factors influencing the structure and content of quality assurance.